2021
DOI: 10.1108/sampj-03-2021-0095
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the informativeness of sustainability disclosures versus ESG disclosure ratings

Abstract: Purpose The purpose of this paper is to examine the impact of sustainability disclosures and disclosure ratings on firm value. This paper compares the informativeness of sustainability disclosures in company reports versus environmental, social and governance (ESG) disclosure ratings. The authors examine the extent to which they provide incremental information. Design/methodology/approach The sample consists of panel data from over 2,600 publicly-listed non-financial US companies for the period 2014–2018. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 53 publications
(74 reference statements)
1
18
0
Order By: Relevance
“…This situation can be explained by the strict legal regulations and mandatory disclosures pushing firms to disclose governance structure‐related information compared to E and S dimensions, which are more voluntary. These findings are also similar to the relevant literature (Eng et al, 2022; Yu & Van Luu, 2021). The firms in the sample have an average of 15.9% female members on their boards of directors.…”
Section: Resultssupporting
confidence: 93%
“…This situation can be explained by the strict legal regulations and mandatory disclosures pushing firms to disclose governance structure‐related information compared to E and S dimensions, which are more voluntary. These findings are also similar to the relevant literature (Eng et al, 2022; Yu & Van Luu, 2021). The firms in the sample have an average of 15.9% female members on their boards of directors.…”
Section: Resultssupporting
confidence: 93%
“…Hypothesis 1 is confirmed, and our results are inconsistent with some authors. For example, a study (Eng and Fikru, 2021) showed that ESG scores are positively associated with market value and price. Sustainability disclosure in the form of metrics and firm-tailored narratives provides the incremental information content on market value and/or price.…”
Section: Jefasmentioning
confidence: 99%
“…Recent studies agree that ESG disclosure increases corporate transparency and hence improves capital investment efficiency by mitigating under-and over-investment problems [8,104]. In addition, there is greater interest in examining the impact of ESG disclosure on ESG ratings [105][106][107][108].…”
Section: Current Topics and Recommendations For Future Researchmentioning
confidence: 99%